EFEK EKOENZIM SEBAGAI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN (TINGGI DAN JUMLAH DAUN) SERTA BIOMASSA (BERAT BASAH DAN KERING) TANAMAN BAYAM (Amaranthus Spp.) - Suwarniati, Suwarniati; Fajriana, Nurul; Zacky, Achmad (FKIP Universitas Tanjungpura, 2026)
Eco-enzyme is a fermentation product of organic waste containing bioactive compounds and nutrients, making it a potential liquid organic fertilizer to enhance horticultural crop growth. This study aimed to evaluate the effect of different eco-enzyme concentrations on the growth and biomass of spinach (Amaranthus spp.). The experiment used a Completely Randomized Design (CRD) with four treatments: P0 (control, without eco-enzyme), P1 (eco-enzyme 5 ml/L), P2 (eco-enzyme 10 ml/L), and P3 (eco-enzyme 15 ml/L), each replicated four times. Data were analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, one-way ANOVA or Kruskal–Wallis according to assumption fulfilment, followed by Tukey HSD or pairwise non-parametric comparison. The ANOVA test results showed significant differences between treatments in the first week (F = 36.085; p < 0.001) and the second week (F = 12.349; p = 0.001). The Tukey HSD follow-up test showed that in the first week, all treatments were significantly different, while in the second week significant differences were only found between P3 and P0 and P1, and P2 and P1. In the third week, the homogeneity assumption was not met (p = 0.013), so the analysis was continued using the Kruskal Wallis test. The results showed a significant difference (p = 0.011), but the follow-up test only confirmed the significant difference between P3 and P1. Fresh and dry weights also showed significant differences, with P1 outperforming P3. In conclusion, applying eco-enzyme at a moderate concentration (5 ml/L) effectively enhanced spinach growth and biomass, whereas higher concentrations reduced its effectiveness.Kata Kunci: eco-enzyme, Amaranthus spp., plant growth, biomass